Exploring Senior High School English Teachers’ Problems of Classroom Management and Their Strategy in Online English Teaching and Learning process: A Case Study - Lutfiana S., Putri; Suharjito, Bambang; Wahjuningsih, Eka (EFL Education Journal, 2024)
During Covid-19 the teaching-learning system is carried out online around the world. In Indonesia, the online learning system is something new. It is undeniable that many obstacles arise when teaching online. The aim of this study was to explore senior high school English teachers’ problems of classroom management and their solutions in online English teaching and learning process. The data collected from two English teacher at senior high school in Jember by using a case study and semi-structured interview to obtain detailed information on the research issue. Based on the results, some factors in classroom management problems faced by teachers were found. They were: Material provision, Technological Issues, Time management, Teacher and Students Interaction and Human Resources. Teachers have to improvised or adapting their method of teaching in short time during online classes to solve the problem. Both of the teachers used a different method of teaching. The first teacher used traditional approach using school radio to broadcast and the second teacher used Jam Board to made an interaction and monitoring the students. Therefore, it is suggested to another researcher who conduct further research on English teachers' problems in classroom management and solutions in the online English learning process, can use this research as a reference. Keywords: Online Classroom Management, Teacher teaching online experienced, Student Interaction.